Control of AC/DC Modular Multilevel Converter - Blahnik, Vojtech; Kosan, Tomas; Peroutka, Zdenek; Talla, Jakub (Elektronika ir Elektrotechnika, 2018)
In recent years, a special attention is paid to grid connected multilevel converters. These converters have specific use in industry in a high power, medium-voltage and high-voltage applications. This paper presents new control algorithm for single-phase AC/DC modular multilevel converter with target application as a traction converter connected directly to trolley wire. The proposed control strategy presents resonant controllers for converter current control with fundamental frequency adaptation. The fundamental frequency estimation and voltage synchronization is based on Second Order General Integrator Phase Locked Loop (SOGI-PLL). Furthermore, this paper presents robust voltage balancing technique for multilevel converter based on energy calculation of DC-link capacitances. It provides voltage balancing of multilevel converter cells with unbalanced load. The resulting control algorithm has low total harmonic distortion of converter trolley current even under unbalanced load condition. The algorithm was experimentally verified on the low voltage laboratory prototype with 3 H-bridge cells.DOI: http://dx.doi.org/10.5755/j01.eie.24.6.22282